Not necessarily detrimental: Two social comparison orientations and their associations with social media use and college social adjustment. (July 2018) - Yang, Chia-chen; Robinson, Angela
Abstract: Social network sites (SNSs) are considered a convenient platform for social comparison. Current SNS social comparison research typically focuses on the activity of SNS browsing, which overlooks other use patterns available in the social media environment. Also, little research recognizes the two-dimensional nature of social comparison. Drawing on literature of social comparison and the activity-audience framework of social media use, we studied social comparison as a personal characteristic (social comparison orientation; SCO) relating to college students' social adjustment via various Instagram activities and interactants. Implications of both dimensions of SCO were explored through survey data from 208 U.S. college undergraduates ( M age  = 19.43, 78% female). Social comparison orientation of ability (SCO-Ability) was related to poorer college social adjustment whereas social comparison orientation of opinion (SCO-Opinion) was related to better adjustment. Both types of SCO had a positive indirect association with adjustment via more frequent Instagram interaction with on-campus friends. SCO-Opinion was related to more Instagram interaction with off-campus friends, which was related to poorer social adjustment, but the overall indirect path was non-significant. Both types of SCO were also related to more frequent Instagram browsing. The study underscores the significance of recognizing SCO as a two-dimensional construct and illustrates how SCO can associate with social well-being in the social media context. Highlights: There are 2 dimensions of social comparison orientation (SCO): Ability & Opinion. SCO-Ability had a direct, negative association with college social adjustment. SCO-Opinion had a direct, positive association with college social adjustment. Both SCOs had an indirect, positive association with adjustment via Instagram use.